2006
DOI: 10.1063/1.2172742
|View full text |Cite
|
Sign up to set email alerts
|

Strain relief by periodic misfit arrays for low defect density GaSb on GaAs

Abstract: Growth of room-temperature "arsenic free" infrared photovoltaic detectors on GaSb substrate using metamorphic InAlSb digital alloy buffer layers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
200
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(213 citation statements)
references
References 15 publications
(7 reference statements)
11
200
2
Order By: Relevance
“…One sample is grown by introducing the IMF arrays at the GaSb-buffer/GaAs heterointerface (QW-IMF), the details of which are presented distinctively elsewhere. 18) The other sample is grown directly on GaAs without the formation of IMF at the interface (QW-No-IMF). The key issue for the difference of the two samples is that GaSb buffer is grown on the Ga-stabilized GaAs surface in the former case and it is grown on the As-stabilized surface in the latter case.…”
Section: Sample Preparation and Measurement Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…One sample is grown by introducing the IMF arrays at the GaSb-buffer/GaAs heterointerface (QW-IMF), the details of which are presented distinctively elsewhere. 18) The other sample is grown directly on GaAs without the formation of IMF at the interface (QW-No-IMF). The key issue for the difference of the two samples is that GaSb buffer is grown on the Ga-stabilized GaAs surface in the former case and it is grown on the As-stabilized surface in the latter case.…”
Section: Sample Preparation and Measurement Setupmentioning
confidence: 99%
“…In the case of the QW-IMF, 98.5% of the strain is reported to be relieved with the insertion of the IMF arrays at the GaSb/GaAs interface. 18) Therefore no strain contribution was considered to calculate the GaSb/AlGaSb QW band structure grown on the strain- …”
Section: Calculation Of Unstrained Qw-imf Band Structure Based On Plmentioning
confidence: 99%
“…In the related case of GaSb on GaAs, Huang et al have observed the coexistence of a pseudomorphic (elastically strained) wetting layer and plastically relaxed metamorphic quantum dots. 2 A TEM overview of the AlSb/GaAs interface is shown in Fig. 2 APPLIED PHYSICS LETTERS 100, 012103 (2012) mismatch is relaxed by 90 dislocations at the interface.…”
mentioning
confidence: 99%
“…After oxide desorption and buffer layer growth, the sample was exposed to Sb at a substrate temperature T s of 600 C until a 8 Â periodicity was observed in the reflection high energy electron diffraction (RHEED) pattern in the [1 10] azimuth, this being indicative of a Sb terminated GaAs surface. 2 The substrate temperature was then lowered to 500 C and AlSb growth was started at 0.25 ML/s in Sb rich conditions (2 Â 10 À6 mbar Sb beam equivalent pressure). The evolution of the accumulated stress during epitaxial growth was monitored in situ by a multi-beam optical stress sensor (MOSS).…”
mentioning
confidence: 99%
“…The IMF growth mode allows material of good crystalline quality to be deposited, "buffer-free," onto lattice-mismatched substrates. 8 Herein, the strain is relieved within several monolayers of the interface by a periodic, self-ordered network consisting purely of 90 edge dislocations. These propagate laterally, rather than into the overlying epilayer, and defect densities as low as 5 Â10 5 cm À2 have been reported for bulk GaSb on GaAs.…”
mentioning
confidence: 99%